Stock exchange in emerging markets: integrated latin america market (MILA) -an opportunity for investment - Farfan, Kurt Burneo (2017)
The paper is an overview about the Integrated Latin America Market (MILA) until December 2014, including the Mexico Stock Market in the analysis. The papers describes how the market has been developing during the last five years, showing some aspects about the market capitalization, the most traded shares and the S&P MILA Andean 40 index. Besides the paper shows the benefits about the MILA to investors and the relation between the stock exchange index and the exchange rate in those markets, using a correlation model.